Impact of antipsychotic review and non‐pharmacological intervention on health‐related quality of life in people with dementia living in care homes: WHELD—a factorial cluster randomised controlled trial. (19th September 2016) - Ballard, Clive; Orrell, Martin; Sun, Yongzhong; Moniz‐Cook, Esme; Stafford, Jane; Whitaker, Rhiannon; Woods, Bob; Corbett, Anne; Banerjee, Sube; Testad, Ingelin; Garrod, Lucy; Khan, Zunera; et al.
Abstract : Background: Very few interventional studies have directly examined the impact of treatment approaches on health‐related quality of life (HRQL) in people with dementia. This is of particular importance in therapies to address behavioural symptoms, where HRQL is often severely affected. Methods: Analysis within the WHELD cluster randomised factorial study in 16 UK care homes examining the impact of person‐centred care in combination with antipsychotic review, social interaction and exercise interventions. This study analysed impact on HRQL through the DEMQOL‐Proxy. Results: Data on HRQL were available for 187 participants. People receiving antipsychotic review showed a significant worsening in two DEMQOL‐Proxy domains (negative emotion: p = 0.02; appearance: p = 0.04). A best‐case scenario analysis showed significant worsening for total DEMQOL‐Proxy score. Social interaction intervention resulted in a significant benefit to HRQL ( p = 0.04). There was no deterioration in HRQL in groups receiving both antipsychotic review and social interaction ( p = 0.62). Conclusions: This demonstrates an important detrimental impact of discontinuation of antipsychotics in dementia on HRQL, highlighting the need for careful review of best practice guidelines regarding antipsychotic use and emphasising the importance of providing evidence‐based non‐pharmacological interventions in conjunction with antipsychotic review. Copyright © 2016 John Wiley & Sons, Ltd.